Comparison of a load bearing capacity for composite sandwich plywood plates (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This article shows numerical investigations of composite sandwich plywood plates with birch plywood faces and a core of straight and curved plywood honeycomb-type ribs in comparison to standard plywood plates and other core type plates. This shape of core ribs provides several improvements for these plates in manufacturing process as well as mechanical properties. The influence of core element shapes on stiffness in longitudinal direction of a plate is insignificant although it is possible to vary with stiffness in transverse direction of these plates by changing form of plate’s ribs. The results are describable as specific strength or stiffness (stiffness to mass or strength to mass ratio etc.) in both directions. The various results depending on chosen variables (according to strength-stiffness criteria) plywood composite macrostructure is obtained for one span plate with uniformly distributed loading. The results show that it is possible to reduce material consumption causing reduction in stiffness but in general increasing stiffness to weight ratio for about 30% or even more if it is possible to increase height of a plate more than maximum standard plywood plate.All thicknesses of elements are chosen according to plywood supplier assortment.A various thicknesses of plywood sheets (0/90/0+90/0·n) are taken for straight ribs as well as various plates coverings for waved part of ribs the 3 layer plywood was taken (90/0/90) or (0/90/0) due to simplification of manufacturing process. For all parts of plate were Birch plywood plates used, as well as reference plywood were Standard Birch plywood plates chosen.